Crisis Resilience and the Role of Islamic Financial Institutions in Regional Development - Hidayaturrahman, Mohammad; Hidayat, Imam; Syahril, Syahril; Syuhri, Saifuddin (PUBLIC CORNER, 2024)
This research was conducted to find out and analyze the role of Islamic financial services, Bank BPRS Bhakti Sumekar and Baitul Maal wat Tamwil (BMT) NU Jawa Timur in sustainable development in region with a majority Muslim population, Sumenep Regency, Madura, East Java. The research model is comparative-qualitative, comparing the two Islamic financial services of Bank BPRS Bhakti Sumekar and BMT NU Jawa Timur in developing structural and cultural-based Islamic financial services. Bank BPRS Bhakti Sumekar is structurally based as a Regional Owned Enterprise (BUMD) for the Sumenep Regency Government. BMT NU Jawa Timur is culturally based, founded, and run by the community. The data collection technique for this research was in-depth interviews, observing activities in the offices and branches of the two financial services. In addition, a search was carried out for relevant documents owned by the two financial institutions and online media and official websites related to the research topic. Focus group discussions were also conducted with Islamic finance experts. The research succeeded in uncovering the role of the two Islamic financial services in sustainable development in Sumenep Regency. Culturally-based Islamic financial services grow faster and are more resilient to economic crises.